Comparison of Plan Quality and Delivery Time Between Volumetric Arc Therapy (RapidArc) and Gamma Knife Radiosurgery for Multiple Cranial Metastases. Issue 4 (27th May 2014) - Thomas, Evan M.; Popple, Richard A.; Wu, Xingen; Clark, Grant M.; Markert, James M.; Guthrie, Barton L.; Yuan, Yu; Dobelbower, Michael C.; Spencer, Sharon A.; Fiveash, John B.
Abstract: BACKGROUND: Volumetric modulated arc therapy (VMAT) has been shown to be feasible for radiosurgical treatment of multiple cranial lesions with a single isocenter. OBJECTIVE: To investigate whether equivalent radiosurgical plan quality and reduced delivery time could be achieved in VMAT for patients with multiple intracranial targets previously treated with Gamma Knife (GK) radiosurgery. METHODS: We identified 28 GK treatments of multiple metastases. These were replanned for multiarc and single-arc, single-isocenter VMAT (RapidArc) in Eclipse. The prescription for all targets was standardized to 18 Gy. Each plan was normalized for 100% prescription dose to 99% to 100% of target volume. Plan quality was analyzed by target conformity (Radiation Therapy Oncology Group and Paddick conformity indices [CIs]), dose falloff (area under the dose-volume histogram curve), as well as the V4.5, V9, V12, and V18 isodose volumes. Other end points included beam-on and treatment time. RESULTS: Compared with GK, multiarc VMAT improved median plan conformity (CIVMAT = 1.14, CIGK = 1.65; P < .001) with no significant difference in median dose falloff ( P = .269), 12 Gy isodose volume ( P = .500), or low isodose spill ( P = .49). Multiarc VMAT plans were associated with markedly reduced treatment time. A predictive model of the 12 Gy isodose volume as a function of tumor number and volume was also developed. CONCLUSION: For multiple target stereotactic radiosurgery, 4-arc VMAT produced clinically equivalent conformity, dose falloff, 12 Gy isodose volume, and low isodose spill, and reduced treatment time compared with GK. Because of its similar plan quality and increased delivery efficiency, single-isocenter VMAT radiosurgery may constitute an attractive alternative to multi-isocenter radiosurgery for some patients.